1987
DOI: 10.1007/s0054070010062
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the epinephrine-induced arrhythmogenic effect of sevoflurane with isoflurane and halothane

Abstract: The effect of sevoflurane on cardiac arrhythmias induced by the infusion of epinephrine into dogs was compared with those of isoflurane and halothane. The arrhythmogenic doses of epinephrine determined in this comparative study were expressed by both infusion rates of epinephrine and the corresponding plasma levels obtained by a series of three-minute epinephrine infusions during sevolurane, isoflurane, and halothane anesthesia at 1.25 MAC. The mean values of the arrythmogenic infusion rates of epinephrine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…15 16 It produces similar degrees of myocardial depression and hypotension to equipotent concentrations of halothane in children 10 and less sensitisation of the myocardium to catecholamines. 17 The degree of respiratory depression is similar to that produced by halothane at equipotent concentrations. 18 19 nificantly reduced or eliminated.…”
Section: Sevofluranementioning
confidence: 77%
“…15 16 It produces similar degrees of myocardial depression and hypotension to equipotent concentrations of halothane in children 10 and less sensitisation of the myocardium to catecholamines. 17 The degree of respiratory depression is similar to that produced by halothane at equipotent concentrations. 18 19 nificantly reduced or eliminated.…”
Section: Sevofluranementioning
confidence: 77%
“…On the other hand, no patient had arrhythmia in the sevoflurane group. Sevoflurane dose not appear to be arrhythmogenic in dogs, and the arrhythmogenic dose of epinephrine exceeds that found during anesthesia with isoflurane [10]. This is an advantage during anesthesia for cesarean section.…”
Section: Discussionmentioning
confidence: 95%
“…The movements were in the form of moderate extremity movements joined by the wrist joint. Immamura et al [14] reported that in patients having sevoflurane anesthesia, the risk of arrhythmia inducted with the adrenaline discharge under hypoxic and hypercarbic conditions was less than in halothane. Sevoflurane and halothane were reported as the most suitable agents in terms of cardiovascular parameters in anesthesia induction with mask [15].…”
Section: Discussionmentioning
confidence: 99%